Professional responsibility of doctors in a legal perspective on fulfilling patients’ health rights during the COVID-19 pandemic in Indonesia - Dwi Ratna Kartikawati, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The COVID-19 pandemic began to enter Indonesia in early 2020, in this case the responsibilities and obligations of doctors are one of the concerns during the pandemic. The responsibility of medicine from a legal perspective is very diverse and implemented in various countries. In Indonesia, to realize the responsibilities, obligations and rights of the medical profession, it can be done through the fulfillment of a code of ethics that needs to be developed in various conditions. This study used a qualitative juridical research model with a review of legal texts and other supporting literature. It is hoped that this research can provide an overview of how the medical profession responds to the phenomenon of the COVID-19 pandemic in Indonesia and the future prospects for professional development and a medical code of ethics.